Public / private mix in pensions in Europe. The role of state, market and social partners in supplementary pensions - Natali, David (Brussels, 2009)
"This Working Paper sheds light on the multi-dimensional and changing interplay between state, market institutions and social partners in relation to supplementary pension schemes, the importance of which is growing across Europe. The paper offers a lucid analysis of the responsibility shared among these three sets of actors to protect against the risk of old age by developing the provision of privately managed fully-funded schemes ."